The mixed-up chameleon : with all new illustrations - Carle, Eric (Puffin Books, 1988)
From Eric Carle, the New York Times bestselling author of The Very Hungry Caterpillar and The Grouchy Ladybug, comes a colorful and inventive book about a changing chameleon that wants to be a little bit of everything. There once was a small green chameleon that wished to be handsome like a flamingo, smart like a fox, and funny like a seal. But with each transformation in size, shape, and color, the chameleon learns that maybe being yourself is best of all! The Mixed-Up Chameleon is sure to delight little readers with its interactive art, funny antics, and heartwarming message. This board book edition is the perfect size for small hands and features sturdy pages.